High Power Density Pyroelectric Energy Conversion in Nanometer-Thick BaTiO3 Films. Issue 3 (1st October 2016) - Bhatia, Bikram; Cho, Hanna; Karthik, J.; Choi, Jangho; Cahill, David G.; Martin, Lane W.; King, William P.
ABSTRACT: Solid-state pyroelectric nanomaterials can be used for thermal-to-electrical energy conversion in the presence of temperature fluctuations. This article reports investigation of energy conversion in a 200 nm thick BaTiO3 film using the pyroelectric Ericsson cycle at cycle frequencies up to 3 kHz. The high cycle frequencies were achieved due to the low thermal mass of the nanometer-scale film, unlike previous studies in which the electrical power output was limited by the rate of heat transfer through the pyroelectric material. A microfabricated platform that allowed precise thermal and electrical cycling enabled us to study the effect of electric field range, temperature oscillation amplitude, and cycle frequency on the electrical power output from pyroelectric Ericsson cycles. We measured a maximum power density of 30 W/cm 3 for a temperature range 20–120°C and electric field range 100–125 kV/cm, which represents a significant improvement over past work on pyroelectric cycles. The approach presented in this article could lead to high-power waste heat harvesting in systems with high-frequency temperature oscillations.